Geomorphological features in the Grda Sur Valley basin in Erbil province - Jihan, Abboud; أ.د إسحق صالح العكام (Journal of College of Education, 2023)
Abstract:      The research aims to study the land forms in the Grda sor valley basin south of Erbil province- Iraq, The study found that geomorphological processes, including water erosion, are highly active in mountain foot areas, especially in areas with fragile rock formation, which is clearly reflected in the compositions of the study area, from which we conclude the activity of mass movement over time, and its speed is associated with the quality of rock composition and the fact that fragile rocks quickly occur in the mass movement, also shows clear progress in water erosion on wind erosion, and classified the terrestrial forms in the study area basin into five geomorphological units. Different forms were (forms of structural-erosional, forms of water- erosional origin, the most prominent of which were padlands, forms of ethnic origin, forms of land resulting from karst melting, and finally land forms resulting from the mass movement.